STRATEGI PEMBELAJARAN SAAT PANDEMI: SURVEI PADA MAHASISWA TELAAH KURIKULUM DAN MATEMATIKA EKONOMI - K. G. Hilmiatussadiah (Jurnal Pendidikan Ekonomi Indonesia, 2020)
Learning objectives must be achieved in every learning avtivity, achieving these goals requires appropriate learning strategies. This study aims to determine the learning startegies in curriculum review and economic mathematics courses that can improve students understanding of teaching materials. The survei was conducted on 92 students of economic education who studied curriculum review and economic mathematics courses with the research method used was descriptive. The results of the study stated that students who studied curriculum review and economic mathematics chose the study face-to-face even though online using the zoom application could improve understanding of the material, basides that, video, audio and other interactive media were also needed that could help students understand the material.